Answer:
y = -7x - 5
Step-by-step explanation:
14x + 2y = -10
2y = -14x - 10
2y/2 = -14x/2 - 10/2
y = -7x - 5
Hope this helps -w-
This is how to solve this
<em>Answer:</em>
<em>r = -</em>
<em />
<em>Step-by-step explanation:</em>
<em>Rewrite the equation as </em>
<em> = m</em>
<em>Remove the radical on the left side of the equation by squaring both sides of the equation.</em>
<em>(</em>
<em> = m^2</em>
<em>Then, you simplify each of the equation. </em>
<em>Rewrite: (</em>
<em> as </em>
<em />
<em>Remove any parentheses if needed.</em>
<em>Solve for r. </em>
<em>Multiply each term by r and simplify."</em>
<em>Multiply both sides of the equation by 5.</em>
<em>6a+r= m^2r⋅(5)</em>
<em>Remove parentheses.</em>
<em>Move 5 to the left of (m
^2) r
</em>
<em>6a+r=5m^2)r</em>
<em>Subtract 5m^2)r from both sides of the equation.</em>
<em>6a+r-5m^2)r=0</em>
<em>Subtract 6a from both sides of the equation.</em>
<em>r-5m^2)r=-6a</em>
<em>Factor r out of r-5m^2)r </em>
<em>r(1-5m^2)=-6a</em>
Divide each term by 1-5m^2 and simplify.
r = - ![\frac{6a}{1-5m^2}](https://tex.z-dn.net/?f=%5Cfrac%7B6a%7D%7B1-5m%5E2%7D)
There you go, hope this helps!
No, you would do 100 - 64 because 10^2 is 100 and 8^2 is 64.
100-64= 36
The square root of 36 is 6. The length of the other leg is 6.
It should take about 13.3 hours